Assessment of Essential Knowledge Components for Real Estate Project Developers in Thailand: An Exploratory Factor Analysis - Nititerapad, Chunyarat (Journal of Cultural Analysis and Social Change, 2025)
This research aims to identify key knowledge areas for real estate project developers and create readiness assessment criteria for the Thai market. Data were gathered from 100 managerial-level personnel in real estate development firms in the Bangkok Metropolitan Area. After removing one outlier, 99 valid responses remained. EFA identified three distinct knowledge components: (1) Marketing and Finance Knowledge, including marketing, project budgeting, and managerial accounting. (2) Strategy and Risk Knowledge, covering strategic management and risk management. and (3) Legal Contracts, Investment, and Services Knowledge, involving contract preparation, investment data analysis, management, and project services. The results show that real estate developers in Thailand need skills across three key knowledge areas. These findings offer a framework for educational programs and professional development activities.